Adipose Tissue Insulin Resistance Is Positively Associated With Serum Uric Acid Levels and Hyperuricemia in Northern Chinese Adults - Sun, Honglin; Chang, Xiaona; Bian, Nannan; An, Yu; Liu, Jia; Leng, Song; Wang, Guang (Frontiers in Endocrinology, 2022)
Objective Adipose tissue plays a crucial role in serum uric acid (UA) metabolism, but the relative contribution of adipose tissue insulin resistance (IR) to serum UA levels and hyperuricemia have not explicitly been illustrated. Herein, we aimed to investigate the association between the adipose tissue insulin resistance index (Adipo-IR) and hyperuricemia in this cross-sectional study. The Homeostasis model assessment of insulin resistance (HOMA-IR) index, another widely applied marker to determine systemic IR, was also explored. Methods A total of 5821 adults were included in this study. The relationship between Adipo-IR or HOMA-IR and serum UA levels was assessed by multivariate linear regression. Binary logistic regression analyses were applied to determine the sex-specific association of the Adipo-IR tertiles and HOMA-IR tertiles with hyperuricemia. Participants were then divided into normal BMI (18.5 ≤ BMI < 24) and elevated BMI (BMI ≥ 24) groups for further analysis. Results Both Adipo-IR and HOMA-IR were positively correlated with serum UA (P < 0.001). Compared with the lowest tertile, the risks of hyperuricemia increased across Adipo-IR tertiles (middle tertile: OR 1.52, 95%CI 1.24-1.88; highest tertile: OR 2.10, 95%CI 1.67 - 2.63) in males after full adjustment (P for trend < 0.001). In females, only the highest tertile (OR 2.09, 95%CI 1.52-2.87) was significantly associated with hyperuricemia. Those associations remained significant in participants with normal BMI status. As for HOMA-IR, only the highest tertile showed positive relationships with hyperuricemia in both genders after full adjustment (P for trend < 0.001). The association between HOMA-IR and hyperuricemia disappeared in males with normal BMI status. Conclusions Adipo-IR was strongly associated with serum UA and hyperuricemia regardless of BMI classification. In males with normal BMI, Adipo-IR, rather than HOMA-IR, was closely associated with hyperuricemia. Altogether, our finding highlights a critical role of adipose tissue IR on serum UA metabolism and hyperuricemia.